Reflection of religious motives in the heroic epic «Manas» - A. A. Bakirov (Nomadic Civilization: Historical Research, 2023)
At the beginning of the I millennium BC, one of the largest events in the history of the peoples inhabiting the mountainous expanses of Eurasia took place — the transition of steppe tribes to a nomadic lifestyle, to nomadic cattle breeding. The presented study examines the heroic epic «Manas» — one of the oldest epics in the world, which reflects not only the life and way of life of the nomadic Kyrgyz people, their ethical norms, but also religious cult rituals and actions.   The main goal of the author is to reveal the religious foundations of the epic «Manas», which made it possible to formulate two key tasks: on the one hand, the identification of peculiar historical «signs of time», traces of various epochs found in the work, and the analysis of religious images of «Manas», on the other.   Both tasks are inextricably linked and reflect, in fact, different sides of the same problem. ьThe author examines in detail the issues of reflection of early religious beliefs (totemism, animism, ancestor cult), as well as Muslim motifs in the epic text. The main purpose of the scientific analysis of religious motifs is to clarify their ontological and axiological value in the context of nomadic existence. The article presents the totemic beliefs on the example of the zoomorphic goddess Ak-Bugu very vividly. It tells how Ak-Bugu (literally, the Holy Deer-girl) feeds baby Semetei with her milk, and his mother seeing it,perceived it as a good sign. In ancient times, the deer, elk, argali, as well as the wolf or the leopard, were considered sacred animals patronizing the Kyrgyz tribes. The researcher also considered one of the most ancient and vivid female characters of the epic Manas, namely Aichuryok. Her image in “Manas” is associated with the motive of hero’s revival by his wife, which is widespread in the epic of Turkic-Mongolian peoples.